58% Dark Chocolate Formulation with Added Spices (Ginger Emprit, Cinnamon and Clove) - Elianarni, Dahlia; Rista Anggriani; Noor Harini; Damat; Betty Abiya Cahyati (Jurnal Teknologi Pangan dan Hasil Pertanian, 2025)
Chocolate is a popular food product. Research and development of chocolate products are increasing to increase their functional value. This study aims to determine the physicochemical and sensory characteristics of 58% dark chocolate with the combined fortification of ginger emprit, cinnamon, and clove to add functional value to chocolate. The research design used was randomized block design. The results showed that the highest water content was in sample C3 (1.51%), antioxidant activity of sample C2 (66.52%), phenol content test of sample C4 (7.00 GAE/g), flavonoid content test of sample C3 (4.96 QE/g), in the water activity test of sample C0 (0.52), in the total plate count of bacteria the most was in C1 which was 3.2 x 104. in texture the highest hardness value was in sample C4 (170.60). In the organoleptic test, the highest assessment in the color parameter was in sample C2 (3.76), in the aroma parameter in sample C0 (3.84), in the texture parameter in sample C4 (2.96), in the taste parameter in sample C2 (3.44), in the liking parameter in samples C2 and C4 (72).